Paradoxical development of neovascular glaucoma following carotid angioplasty and stenting - Lee, Kyung Mi (Interv Neuroradiol, 2016)
This report describes a very rare ocular complication of carotid intervention. A 74-year-old patient presented with left-sided weakness and was diagnosed with right cerebral border-zone infarctions caused by severe stenosis of the right proximal internal carotid artery. Staged carotid intervention (balloon angioplasty followed by stenting) was successfully performed. However, neovascular glaucoma developed following carotid angioplasty and stenting. We concluded that although carotid angioplasty and stenting improves vision in patients with ischemic oculopathy, it can rarely induce paradoxical visual deterioration such as development or aggravation of neovascular glaucoma.